Pengaruh Pemberian Terapi Nebulizer terhadap Peningkatan Saturasi Oksigen pada Pasien Bronkopneumonia di UGD RSAU Dr. Dody Sardjoto - Pricilia Rosario B; Hamzah Tasa; Kade Wijaya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Bronchopneumonia is a lower respiratory tract infection that remains a major health problem, especially in children, which can cause impaired gas exchange and ultimately decrease oxygen saturation. This condition, if not immediately treated, can lead to hypoxia and improve the patient's clinical condition. One intervention frequently administered in the emergency room is nebulizer therapy, which functions to help widen the airways, reduce secretion production, and improve pulmonary ventilation. This study aims to determine the effect of nebulizer therapy on increasing oxygen saturation in bronchopneumonia patients in the emergency room of Dr. Dody Sardjoto Air Force Hospital. This study used a quasi-experimental design with a one-group pretest-posttest approach. The study sample was bronchopneumonia patients who received nebulizer therapy intervention in the emergency room. The results showed an increase in oxygen saturation after nebulizer therapy with a p-value of 0.000 (p < 0.05), indicating a significant effect. Thus, nebulizer therapy is proven effective in increasing oxygen saturation and can be used as a treatment intervention in the management of oxygenation disorders in bronchopneumonia patients.